Association of air pollution exposure with low arousal threshold obstructive sleep apnea: A cross-sectional study in Taipei, Taiwan. (1st August 2022) - Qiu, Hong; Liu, Wen-Te; Lin, Shang-Yang; Li, Zhi-Yuan; He, Yan-Su; Yim, Steve Hung Lam; Wong, Eliza Lai-Yi; Chuang, Hsiao-Chi; Ho, Kin-Fai
Abstract: Emerging evidence witnesses the association of air pollution exposure with sleep disorders or the risk of obstructive sleep apnea (OSA); however, the results are not consistent. OSA patients with or without a low arousal threshold (LAT) have different pathology and therapeutic schemes. No study has evaluated the potential diverse effects of air pollution on the phenotypes of OSA. The current study aimed to evaluate the associations of short-term and long-term exposure to air pollution with sleep-disordered measures and OSA phenotypes. This cross-sectional study consisted of 4634 participants from a sleep center in Taipei from January 2015 to April 2019. The personal exposure to ambient PM2.5 and NO2 was assessed by a spatial-temporal model. Overnight polysomnography was used to measure the sleep parameters. According to a developed clinical tool, we defined the low arousal threshold (LAT) and identified the OSA patients with or without LAT. We applied a generalized linear model and multinomial logistic regression model to estimate the change of sleep measures and risk of the OSA phenotypes, respectively, associated with an interquartile range (IQR) increment of personal pollution exposure after adjusting for the essential confounders. In the single-pollutant model, we observed the associations of NO2 with sleep-disordered measures by decreasing the total sleep time, sleep efficiency, extending the time of wake after sleep onset, and the association of NO2 with the increased risk of LAT OSA by around 15%. The two-pollutant model with both long-term and short-term exposures confirmed the most robust associations of long-term NO2 exposure with sleep measures. An IQR increment of NO2 averaged over the past year (6.0 ppb) decreased 3.32 min of total sleep time and 0.85% of sleep efficiency. Mitigating exposure to air pollution may improve sleep quality and reduce the risk of LAT OSA. Graphical abstract: Image 1 Highlights: Personal exposure to ambient PM2.5 and NO2 was assessed by a spatial-temporal model. Polysomnography was used to identify sleep-disordered measures and OSA phenotypes. NO2 was associated with decreased sleep duration and efficiency. NO2 was associated with the increased risk of low arousal threshold OSA.